2010
DOI: 10.1007/s11356-010-0343-x
|View full text |Cite
|
Sign up to set email alerts
|

Pollution in coastal fog at Alto Patache, Northern Chile

Abstract: We found no direct indication for the importance of other sources such as the emission of dimethyl sulfide from the ocean and subsequent atmospheric oxidation for acidity and sulfate or soil erosion for heavy metal concentrations. When fog water was collected by the LFC, it apparently picked up large amounts of dry deposition which accumulated on the nets during fog-free periods. This material is rinsed off the collector shortly after the onset of a fog event with the water collected first. During the first fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 13 publications
3
36
0
5
Order By: Relevance
“…pH values during both the first flush and steady state conditions (measured in a single fog event each) are within the range specified by the WHO and are thus similar to those reported by Gandhidasan and Abualhamayel (2012), Shanyengana et al (2002) and Abdul-Wahab et al (2007b). Schemenauer and Cereceda (1992) and Sträter et al (2010) report much lower (acid) pH values for two Chilean sites.…”
Section: Water Qualitysupporting
confidence: 80%
See 2 more Smart Citations
“…pH values during both the first flush and steady state conditions (measured in a single fog event each) are within the range specified by the WHO and are thus similar to those reported by Gandhidasan and Abualhamayel (2012), Shanyengana et al (2002) and Abdul-Wahab et al (2007b). Schemenauer and Cereceda (1992) and Sträter et al (2010) report much lower (acid) pH values for two Chilean sites.…”
Section: Water Qualitysupporting
confidence: 80%
“…However, Schemenauer and Cereceda (1992) found extremely low pH values in fog water from the El Tofo site in Chile. While in their study, ion and trace element concentrations were generally acceptable, Sträter et al (2010) later additionally found high sulfate concentrations and heavy metal enrichment factors at another Chilean site. Their analysis suggests that even for a remote site, the water quality may be influenced by far-away emission sources, which are passed by the air masses before reaching the collection site.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Acceptable fog water quality was also reported for South Africa (Olivier and van Heerden 2002). However, Sträter et al (2010) report that enhanced concentrations of some ions and metals were found at a coastal site in Chile. They hypothesize that power plant and industrial plant emissions on the west coast of South America exhibit an influence on the chemical composition of fog water.…”
Section: Fog Water Qualitymentioning
confidence: 95%
“…The natural sources of heavy metals in the environment are metal corrosion, volcanic eruption, weathering, soil erosion, leaching and sediment re suspensions. The anthropogenic activities for heavy metal exposure are refineries, coal burning in power plants, high tension lines, textiles, plastic, microelectronics, and wood preservation and paper processing plants [11][12][13][14][15][16][17][18]. Conventional method used for the removal of metals and heavy metals from water or waste water are chemical precipitation, carbon adsorption, ion exchange, evaporations and membrane processes, ultra filtration, electro winning, pre concentration and reverse osmosis [19][20][21][22].…”
mentioning
confidence: 99%